Physical rehabilitation in osteochondrosis of the lumbar spine, complicated unstable segments and intervertebral disc protrusions - Bahjat Al Mahmoud Mavazhdeh. Sohib (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Shows the effect of physical rehabilitation to restore patients with lumbar osteochondrosis with instability segments and intervertebral disc protrusions. In єksperimente participated in 60 patients aged 24-70 years, divided into main and control groups of 30 people each. The survey was conducted on patients' clinical stage of rehabilitation in acute, sub-acute and remission for 20 days at admission (before treatment, on the 10th and 20th day of treatment). It is proved that the developed program of physical rehabilitation is effective recovery of patients is higher than the program of hospital where they were treated. It is noted that the rehabilitation program helps to reduce pain, restore mobility of the lumbar spine, improving the sustainability of elderly patients, reducing travel time distance 50m, raising confident sion in walking distance to the passage of an increase in the pain.